Jaspine B (pachastrissamine) and 2-epi-jaspine B: synthesis and structural assignment - Abraham, E; Davies, S; Roberts, P; Russell, A; Thomson, J (2008)
Jaspine B (pachastrissamine), which was isolated in 2002, is a naturally occurring anhydrophytosphingosine which displays potent biological activity, and as such has attracted much attention from synthetic chemists in recent years, with 14 syntheses reported to date. This review delineates the isolation of jaspine B, and laboratory total syntheses of jaspine B, 2-epi-jaspine B and analogues, which serves to confirm their structure and stereochemistry. © 2008 Elsevier Ltd. All rights reserved.